Increased production of cosmogenic 10 Be recorded in oceanic sediment sequences: Information on the age, duration, and amplitude of the geomagnetic dipole moment minimum over the Matuyama–Brunhes transition - Simon, Quentin; Thouveny, Nicolas; Bourlès, Didier; Bassinot, Franck; Savranskaia, Tatiana; Valet, Jean-Pierre (Earth and Planetary Science Letters, 2018)
International audience New high-resolution authigenic Be-10/Be-9 ratio (Be-ratio) records covering the last geomagnetic reversal, i.e. the Matuyama-Brushes transition (MBT), have been obtained and set on a time scale using benthic delta O-18 (Cibicides wuellerstorfi) records. The geographic distribution of the four studied sites allows global comparison between the North Atlantic, Indian and Pacific Oceans. All Be-ratio records contain a twofold increase triggered by the geomagnetic dipole moment (GDM) collapse associated with the MBT. The stratigraphic position of the Be-ratio spike, relative to marine isotope stages, allows establishment of a robust astrochronological framework for the MBT, anchoring its age between 778 and 766 ka (average mid-peaks at 772 ka), which is consistent with all other available Be-10-proxy records from marine, ice and loess archives. The global Be-10 atmospheric production doubling represents an increase of more than 300 atoms m(-2) s(-1) that is compatible with the increased magnitude of atmospheric Be-10 production obtained by simulations between the present GDM and a null-GDM. The minimum Be-10-derived GDM average computed for the 776-771 ka interval is 1.7 +/- 0.4 x 10(22) Am-2, in agreement with model simulations and absolute paleointensities of transitional lava flows